The Ontario Christian Gleaners: A Case Study of a Stakeholder-Engaged Organizational Strategy - van Duren, Erna; Hansen Sterne, Rita (Cuizine)

(untitled) (McGill University Library, 2014)
The Ontario Christian Gleaners (OCG) gathers, dries, and distributes produce destined to be waste and creates value by processing dried soup mixes and fruit snacks using volunteer labour. This case study examines the roles of relationships in the OCGs strategy, operations, and management using a strategic management framework that incorporates value creation and trading. Data was collected from secondary sources, site visits, and interviews. The case examines how relationships with primary and secondary stakeholders are managed to create value.  Primary stakeholders are individuals, groups, and organizations with formal, regular, contractual or transactional relationships with an organization. At OCG they include donors of vegetables and fruit, supplies like pails, and services like free waste tipping; communities that receive the dried soups, fruits, shipping barrels, and pails; mission and relief organizations that raise funding and distribute the food and the volunteers who donate their time.  Secondary stakeholders do not have regular relationships with an organization but may be affected by its actions or affect its actions indirectly through their activities in the market or society. At OCG secondary stakeholders include those who receive soup; interest groups such as food businesses, consumer or environmental organizations; the earth that supplies the agricultural and food resources; the media; the government that oversees the charitable status requirements and food safety legislation; food banks and others who have similar missions to feed the hungry; and finally educational, social, and health institutions who have goals that intersect with those of the OCG.